O impacto do argumento saudável sobre consumidores de alimentos da classe C do Rio de Janeiro - Mação, Luiz Carlos Ferreira (2014)
The growing technological development and the increasing development of medical science, provide findings that converge on good eating habits, with the goal of a longer and healthier life. Several ingredients are promoted by the food industry as healthy attributes. Little is known about the strength and the impact of these attributes to the consumer. Few studies aiming to study the impact of the presence of healthy argument on consumers and comparatively consumer opinion across the packaging of products that do not have such arguments. This paper examines the attitude of 335 consumers, college students in Class C, with the impact of healthy argument present in food packaging. The choice of class C is due to the growing increase in power consumption in its class. The study showed little impact on the group that viewed the packaging attribute healthy, compared to the group that viewed the packaging without the healthy attribute. The original sample was slightly impacted by the presence of healthy attribute, despite the perception front awareness of the need to search, increasingly, for food seen as healthier. The study examined the characteristics and habits of consumers Class C. Among the main issues explored, the study sought to point out issues such as: the perception of respondents about the presence of healthy attribute in the package; conscious healthy relationship between product attributes displayed on the packaging and the product; The presence of healthy attribute is determinant in consumer purchase intent or determines the concept about food. In short, do an analysis before the attitudes, opinions and perceptions of consumers in the decision to purchase food. The methodology chosen for this assignment was quantitative, based on representative samples, by applying statistical analysis to the result.